2011
DOI: 10.3354/meps08980
|View full text |Cite
|
Sign up to set email alerts
|

Yo-yo vertical movements suggest a foraging strategy for tiger sharks Galeocerdo cuvier

Abstract: Many pelagic fishes exhibit 'yo-yo' diving behavior, which may serve several possible functions, including energy conservation, prey searching and navigation. We deployed accelerometers and digital still cameras on 4 free-ranging tiger sharks Galeocerdo cuvier, to test whether their vertical movements are most consistent with energy conservation or prey searching. All sharks swam continuously, with frequent vertical movements through the water column at mean swimming speeds of 0.5 to 0.9 m s -1 . Tail-beating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 33 publications
(1 reference statement)
10
129
1
3
Order By: Relevance
“…Consequently, blue sharks may be able to feed on them while performing deep, fast movements through the water column. In fact, burst swimming and prey capture events were observed during consecutive V-shaped dives ("yo-yo") in tiger sharks (Nakamura et al, 2011).…”
Section: Dive Shape Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, blue sharks may be able to feed on them while performing deep, fast movements through the water column. In fact, burst swimming and prey capture events were observed during consecutive V-shaped dives ("yo-yo") in tiger sharks (Nakamura et al, 2011).…”
Section: Dive Shape Characterizationmentioning
confidence: 99%
“…Archival tags, in particular, can record data at high temporal resolutions (sub-second) and have been used to determine movements and environmental preferences, identify behavioral patterns such as seasonal migrations or diel changes (Schaefer et al, 2007;Walli et al, 2009;Humphries et al, 2010;Gleiss et al, 2011bGleiss et al, , 2013Nakamura et al, 2011;Queiroz et al, 2012;Afonso and Hazin, 2015;Campana et al, 2015) and also, understand the underlying observed spatial dynamics (Sims et al, 2006(Sims et al, , 2008 and interactions with fisheries (Queiroz et al, 2016). Linking movement patterns to habitat use remains, however, a challenging task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillatory behavior typically occurred within relatively confined areas (i.e., 100 to 200 m) of high prey density and proximal to complex topographical features (i.e., reefs and river mouths). Increased vertical activity has been shown to be associated with active foraging in several pelagic fishes (Sepulveda et al, 2004;Bestley et al, 2010;Nakamura et al, 2011), and crepuscular periods have been shown to be consistently important foraging times for many species (Holland et al, 1996). Although this work was not able to verify feeding activity, the observation of tagged roosterfish pursuing prey at the surface in as little as 9 h after release suggests that some of the behaviors recorded in this study are representative of foraging patterns.…”
Section: Depth Distributionmentioning
confidence: 77%
“…Although this observation does not assure longer-term survival, postrelease feeding is a critical step that must occur in order to facilitate recovery (Aalbers et al, 2004;Cooke & Schramm, 2007;Meka & Margraf, 2007). We also observed repeated periods of increased vertical movements (oscillations) during the track sessions, behaviors that have been shown to be associated with foraging activity in several pelagic species (Carey & Lawson, 1973;Pepperell & Davis, 1999;Sepulveda et al, 2004;Cartamil et al, 2010;Nakamura et al, 2011). These behaviors also contrast the unidirectional movements commonly associated with moribund behavior (Moyes et al, 2006;Heberer et al, 2010).…”
Section: Survivorshipmentioning
confidence: 83%